PEMEROLEHAN PRAGMATIK DALAM BAHASA ANAK STUDI KASUS PRINSIP KERJA SAMA – MAKSIM GRICE PADA ANAK USIA ENAM (6) TAHUN - Qorinta Shinta (Universitas Stikubank (UNISBANK) Semarang, 2010)
A Lecturer at STMIK PROVISI Semarang The study is aimed at describing to what extent Maxim Grice Cooperation Principles affect a child in her interaction/ answering questions, what maxims were violated and what possible factors cause that also to what extent she employed hedges in her answers. The Maxim Grice under investigation was maxim of quantity, maxim of quality, maxim of relevant, and maxim of manner. The subject of this research was a six year old child studying at the first grade of Sompok Elementary School. The data were collected from 3 interviews and 1 phone conversation. The data were recorded and then transribed to be further analyzed. The data reveals that a six year old child was quite aware not to violate Maxim Grice ( quantity, quality, and manner) by delivering straight forward answers. The violation to maxim of quality, quantity, and relevant that did occur showed that she had little knowledge of the topics. However, the use of hedges by the child also showed that she actually tried to obey maxim of quality since she was not certain about the accuracy of the informatin she gave. Key Words : Maxim Grice, Hedges, violate